FILSAFAT KETUHANAN DALAM BHAGAVAD GITA - Putu Sri Marselinawati (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
In the Hindu literature the Bhagavad Gita is one of the books that discusses the conception of God, which is in harmony with the philosophy of the Process or Philosophy of the Organizations of A.N.Whitehead. Etymologically, Bhagavad Gita is said to come from the words Bhagavad and Gita, Bhagavad means God and Gita means singing, So Bhagavad Gita is the song of God. In the discussion of God according to the Philosophy of Organisms or Process Philosophy, it will explain 4 processes, first God and creativity which means God as creator, this is mentioned in the Bhagavad Gita, "God the creator of everything", the second, God as the actual entity, mentioned that God is the source and animates every creation, as stated in the Bhagavad Gita "He is the seed of everything", the third in the framework of the philosophical concept of God concerning the nature and relevance of God in contemporary life, referred to in the Transcendent Bhagavad Gita, God remains spiritual and inaccessible to useless minds but is also immanent which means that it exists in every creation and has a versatile form of brahman, fourth is aboutGod and manisfestation called eternal objects.